PRIVATISASI STRUKTUR KEPEMILIKAN, DAN KINERJA BUMN DI INDONESIA - Usri, Abdul Kadir (Fakultas Ekonomi, UIN Maliki Malang, 2014)
One of the measures to improve the productivity and efficiency of BUMN isprivatization. Privatizationis considered successful if it can improve efficiency, decrease the price or service improvements and performanceenhancements. The population in this study are all state-owned enterprises to be privatized using the InitialPublic Offering (IPO) from the period 1991 to 2004. The analysis method used in this research is multiple linearregression. The results showed (1) public ownership is partially significant effect on the performance ofBUMN after privatization as measured by ROS, ROI, ROE, and SALEFF, so the proposed hypothesis provedcorrect. The influence of public ownership of the largest BUMN performance after privatization is shown bythe measured performance using ROS and the smallest is SALEFF. (2) The prospective share holders with ROSgreat interest, as this is one indicator of the success of a company, the company’s sales performanceimprovement and management can manage BUMN well after privatization (3) SALEFF is a measure ofperformance (efficiency of operations) thats hows the efficiency of sales or revenues, measured using aweighing between sales or income by the number of employees BUMN privatization proceeds. The prospectiveshare holders interested SALEFF great because it shows more efficiency operation BUMN privatizationresults, which compare sales or revenue to the number of employees who work in there.